Concepções do psicossocial e a política de saúde mental brasileira - Felix, Thiago Sousa (2017)
Historically approached by a scientific line focused on the institutionalization of the bearer of psychic suffering, mental health changed with the advance of the Psychiatric Reform. The Centro de Atenção Psicossocial – CAPS [Center for Psychosocial Attention] has become a symbol for the new policy and has contributed for transforming the entire plastered representation of psychic suffering associated to the asylum. This study has the objective to investigate the term “psychosocial” since its origin, as well as its course both on social and health science. For this purpose, two types of research were employed: bibliographic and documental. Methodology was divided into three moments: first, a literature revision by collecting authors who approach the discussion of the word “psychosocial” associated to social psychology; an articulation among psychology, philosophy, social sciences and health sciences authors who approach the psychosocial in its interdisciplinary and questioner implication of the biomedical practice; and, finally, an analysis of official documents of the Brazilian state that included the word “psychosocial”. The diversity of conceptions for the term contributed to a broad perception of it, in line with a definition of health worldly spread. While the theories of social psychology contributed for diverse conceptions of the psychosocial, health sciences formulated the term psychosocial attention. This syntagm was consolidated as a denomination of health strategies that intended to transform the look at mental health and patient. However, this was not followed by a wider comprehension of concepts such as psychosocial rehabilitation, essential expression to understand the insertion of psychosocial attention in the Brazilian health policy. It was found a limited assimilation within the public policy, as well as a dissociation between the political-bureaucratic debate and the academic-scientific one. The theoretical approach of the psychosocial conception, at the same time, points out many practical perspectives and shows the power of the psychosocial idea, consecrating the term in its polysemic meaning.